Europe since 1715 : - Weber, Eugen (Norton, 1972)
This book is a compromise between historical narrative, synthesis, and analysis. It is divided into two major parts, the revolutionary period 1715-1848, during which the ideological and industrial base of the contemporary world evolved; then, the most recent period, an age of masses in material as in human terms, ending in our own day. Each of these sections begins with some chapters that give an overview of the continent and the world in which the events that it describes took place; the economic background, the atmosphere, the mentality of the times